2021
DOI: 10.3311/ppci.18386
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Optimum Tuned Mass Damper for High-rise Structures Considering Soil-structure Interaction

Abstract: The present paper focuses on the optimum design of tuned mass damper (TMD) as a device for control of the structures. The optimum free vibration parameters such as period and damping ratio depend on the soil condition. For this reason, the seven meta-heuristic algorithms namely colliding bodies optimization (CBO), enhanced colliding bodies optimization (ECBO), water strider algorithm (WSA), dynamic water strider algorithm (DWSA), ray optimization (RO) algorithm, teaching-learning-based optimization (TLBO) algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Recent studies 3–15 have incorporated the SSI effect in the dynamic analysis of structures. For instance, Hokmabadi et al 16 discussed the SSI effect on deep foundations through shaking table tests on 5, 10, and 15‐storey buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies 3–15 have incorporated the SSI effect in the dynamic analysis of structures. For instance, Hokmabadi et al 16 discussed the SSI effect on deep foundations through shaking table tests on 5, 10, and 15‐storey buildings.…”
Section: Introductionmentioning
confidence: 99%
“…For a 40-story benchmark structure considering SSI effects, Bekdaş et al (Bekdaş and Nigdeli, 2017) employed harmony search algorithm and bat algorithm to minimize the maximum displacement of structure, and harmony search, flower pollination algorithm, teaching, learning based optimization, Jaya algorithm and two new versions of it were used to minimize the amplitude of the acceleration transfer function (Bekdaş et al, 2019); Salvi et al (2018) adopted a classical nonlinear gradient-based optimization algorithm for the optimization of Root Mean Square top-storey displacement; Etedali et al (2019) realized the greatest decrease of the maximum floor displacement by a multi-objective Cuckoo Search (CS) algorithm; Soheili et al (Soheili et al (2020) reduced the maximum drift of structure using Ant Colony Optimization method. Araz et al (2022a) and (Kaveh and Ardebili, 2021) discussed the effects of different objective functions and meta-heuristic algorithms on the control performance of TMD in SSI system, respectively. Fu et al (Jia and Jianwen, 2019) developed a three-dimensional model to analyze the performance degradation of TMD caused by ignoring SSI, founding that the TMD well-tuned to the system frequency of SSI performed better.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have been focusing on this issue. (See, for example, Mylonakis and Gazetas [16], Mekki et al [17], Oz et al [18], Arboleda-Monsalve et al [19], Liu et al [20] and Kaveh and Ardebili [21]). They concluded that not only does the nature of the soil influence the behavior of the structure, but also that the structure influences the behavior of the soil.…”
Section: Introductionmentioning
confidence: 99%